Qualitative Analysis Of Bottled Drinking Water And Refilled Drinking Water Sold Around University Of Muhammadiyah - Rusidah, Yunita; Farikhah, Lailatul; Mundriyastutik, Yayuk (Prosiding University Research Colloquium, 2021)
This study aims to determine the quality of bottled drinking water and refilleddrinking water that sold around University of Muhammadiyah Kudus.It is in terms ofphysical, chemical, and microbiological parameters of drinking water based on SNI 01-3554-2006 and PMK no. 492 of 2010.The test was conducted byten samples of mineral water. Those are seven bottleddrinking water (Ades, Airmu, Aqua, Cleo, Crystalin, Le mineral and Vit) and three samplesof AMIU was taken from refill drinking water depots around campus, from depots inPasuruhan, Prambatan, and Purwosari. The research was conducted at PT SarigunaPrimatirta Kudus. It is a factory inKudus city which has testing requirements. The testscarried out chemical physics which included testing of TDS, pH, and three heavy metalelements and included testing of content of Fe, Mn and Cl2 (chlorine) elements, andmicrobiology namely TPC of presence of E-coli and Total Coliform.The results of physical and chemical measurements through total dissolved solid(TDS) showed that Airmu and Cleo under 10 ppm (demineral) and below 500 ppm for 8samples of mineral water.It is according to the TDS requirements of SNI, > 10 ppm fordemineralized and> 500 ppm for mineral water. The results of the pH test or the degree ofacidity are in normal pH which are around 7 of 9 samples and only one with an alkalinecondition is 8.37, namely sample from the Pasuruhan depot. The test for the presence ofheavy metals, Fe, Mn,is in good condition, showing the number zero with the brand testkit. In addition, for testing the presence of chlorine content, the results were above thethreshold, namely 0.05 ppm from the Pasuruhan depot water sample, 0.02 ppm from thePrambat depot and the Purwosari depot. This is not in accordance with SNI provisions forchlorine content of 0 ppm. Meanwhile, microbiologically of the TPC showed before dilutionwere only Cleo and Ades which were suitable for consumption because they were absentfrom bacterial contamination. While the TPC results after dilution, testing the differencebetween E-Coli and Total coliform resulted in 7 samples of bottled drinking water whichwere safe and feasible as drinking water according to SNI 01-3553-2006 and 3 samplesAMIU were not fulfilled to PMK No. 492/2010 as drinking water requirements.